Choline supplementation regulates gut microbiome diversity, gut epithelial activity, and the cytokine gene expression in gilts - Zhan, Xiaoshu; Fletcher, Lauren; Huyben, David; Cai, Haiming; Dingle, Serena; Qi, Nanshan; Huber, Lee-Anne; Wang, Bingyun; Li, Julang (Frontiers in Nutrition, 2023)
Choline is an essential nutrient that is necessary for both fetal development and maintenance of neural function, while its effect on female reproductive development is largely unexplored. Our previous study demonstrated that choline supplementation promotes ovarian follicular development and ovulation, although its underlying mechanism was unclear. To uncover the potential regulation pathway, eighteen female Yorkshire × Landrace gilts were fed with either standard commercial diet (Control group, n=9) or choline supplemented diet (Choline group, additional 500mg/kg of control diet, n=9) from day 90 of age to day 186. At day 186, feces samples were analyzed for effects on the gut microbiome using 16S ribosomal RNA gene V3-V4 region sequencing with Illumina MiSeq, serum samples were analyzed for trimethylamine (TMA) and trimethylamine-N-oxide (TMAO) using HILIC method, and jejunum tissues were analyzed for immune related gene expression using qRT-PCR. Our results show that choline supplementation did not alter the circulating level of TMA and TMAO (P>0.05), but rather increased gut microbiome alpha diversity (P<0.05). Beta diversity analysis results showed that the choline diet mainly increased the abundance of Firmicutes, Proteobacteria, and Actinobacteria, but decreased the abundance of Bacteroidetes, Spirochaetes and Euryarchaeota at the phyla level. Meta-genomic analysis revealed that choline supplementation activated pathways in the gut microbiota associated with steroid hormone biosynthesis and degradation of infertility-causing environmental pollutants (bisphenol, xylene and dioxins). To further verify the effect of choline on intestinal activity, a porcine intestine cell line (IPEC-J2) was treated with serial concentrations of choline chloride in vitro. Our data demonstrated that choline promoted the proliferation of IPEC-J2 while inhibiting the apoptotic activity. qRT-PCR results showed that choline significantly increased the expression level of Bcl2 in both IPEC-J2 cells and jejunum tissues. The expression of IL-22, a cytokine that has been shown to impact ovarian function, was increased by choline treatment in vitro. Our findings reveal the beneficial effect of choline supplementation on enhancing the gut microbiome composition and intestinal epithelial activity, and offer insights into how these changes may have contributed to the ovarian development-promoting effect we reported in our previous study.